Ч.Баудений Монгол-Англи толь бичигийн тухай - Л.Чулуунбаатар (Acta Mongolica, 2014)
Charles Bawden is a world-famous Mongolist who compiled and translated many books in his lifetime. Among his valuable works, Mongolian-English Dictionary played an important role. He spent 34 years on compiling this dictionary. At the end of 1980’s he almost finished his hard work. However, as Mongolia was in the period of glasnost at that time, many old pieces of vocabulary could be restored in the Mongolian language. Bawden did not want to leave those words and worked hard again for another 10 years. Thus, numerous essential words related to Mongolian customs, tradition, history, nomadic life style, Mongolian Buddhism and shamanism were added. Cleaves F.W., when commenting on a famous scholar Lessing F.D who compiled Mongolian-English Dictionary in 1960, said that “Ferdinand D.Lessing has put Mongolian study at the high level all over the world by his excellent and comprehensive dictionary.” We, the Mongolians highly prized Bawden’s dictionary, considering it to be an invaluable piece of work for the Mongolian studies. The reason for that is that it included lots of words and expressions that have never been included in previous dictionaries. I would like to mention a simple example. As we look up a compound word ‘уулын ам’, the translation which follows is: ‘mountain valley, valley’